Determining the Tourism Comfort Climate of the Mangrove Forests of Nayband ‎Bay Based on Baker and Terjong Indices - Zahra Hatef Rabiee; Afshin Danehkar; Mohammad Kaboli; Parvaneh Sobhani (Nīvār)
Determining the comfortable climate of each area plays a very important role in the development ‎and growth of tourism. In this study, according to the tourist acceptability of the area and the ‎variety of recreational activities, it is necessary to investigate the right time for the presence of ‎tourists as well as the development of tourism activities in this area. Accordingly, in the present ‎study, the comfort climate of tourism was examined using Baker and Terjung indices. The data ‎collection was done through the Meteorological Organization and Bushehr Asaluyeh station for 22 ‎years (2020-2022). The results of the Baker index showed that in this region, 5 months of the year, ‎including January, February, March, November, and December, the environmental conditions for ‎recreational activities are mild and pleasant days with cool nights, as well as hot and tolerable days ‎with mild nights. And pleasant, suitable. According to the results obtained from Tarjung (day and ‎night comfort coefficient, wind effect coefficient during day and night), the best time for ‎sightseeing in this area is the months of November, December, February, and March for tourism in ‎this area. Considering that the studied area is a protected area, determining the right time for tourism ‎can help to plan correctly to attract tourists and generate income for local communities along with ‎protecting this area as much as possible.‎